The traveller's prayer - Khan, Saniyasnain (Goodword Bks Place of publication not identified, 2011)
The Traveler's Prayer is a heartfelt narrative that follows a journeyer as they embark on an adventure, exploring themes of faith, safety, and the importance of seeking divine guidance while traveling through life's uncertainties.